The Application of Integrating Psychological Regulation with Classroom Sports in English Teaching - Yanhua Lu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The integration of sports and psychological regulation in English teaching can improve students' language skills as well as increase their interest and confidence in learning English. To investigate the implementation of classroom sports integration and psychological regulation in English language instruction. This study employed t-tests and other statistical techniques to analyse the self-efficacy data and academic performance data of students before and after the experiment. Data processing was conducted using SPSS 12.0 statistical software. A random sample of 200 freshmen majoring in English was selected from a specific university. The scale utilises a five-point scoring system, with 1 representing full compliance, 2 representing partial compliance, 3 representing minimal compliance, 4 representing partial non-compliance, and 5 representing full non-compliance. There is a positive correlation between scores and self-efficacy. In general, students with high physical self-efficacy demonstrate superior physical performance, whereas those with low physical self-efficacy exhibit poorer physical performance. The relationship is reciprocal. This suggests that having a strong belief in one's ability to succeed in physical education is associated with achieving positive learning outcomes in the subject. Additionally, achieving positive learning outcomes in physical education may also contribute to the development of a strong belief in one's ability to succeed in the subject. Incorporating psychological regulation into classroom sports has been found to be advantageous in enhancing students' technical skills and test scores, particularly among intermediate and disadvantaged students.